Analisis Tingkat Pendapatan dan Kesejahteraan Pelaku Usaha di Wisata Danau Sipin Kota Jambi - Rizky Adiansyah; Selamet Rahmadi; Jaya Kusuma Edy (Jurnal Ekonomi dan Pembangunan Indonesia, 2026)
This study aims to analyze the socio-economic characteristics, income levels, and welfare levels of business actors at Lake Sipin Tourism, Jambi City. A descriptive survey approach was employed, involving 50 business actors as the sample selected through a saturated sampling technique. Data were collected using structured questionnaires, while descriptive analysis based on criteria established by the Central Statistics Agency was applied as the primary analytical tool. The findings reveal that the socio-economic profile of business actors is predominantly female, with an average age of 42 years, a senior high school educational background, and operating food-based businesses independently with considerably limited capital. In terms of income, the average monthly net income of Rp2,486,000 falls within the moderate category according to the Central Statistics Agency criteria, although 40% of respondents still belong to the low-income group. Meanwhile, the welfare level was measured through the proportion of food consumption expenditure relative to total household expenditure, which reached 48.41% per month, placing the majority of business actors within the moderate welfare category overall.